Paste extrusion 3D printing and characterization of lead zirconate titanate piezoelectric ceramics. Issue 15 (1st August 2021) - Hall, Samuel E.; Regis, Jaime E.; Renteria, Anabel; Chavez, Luis A.; Delfin, Luis; Vargas, Sebastian; Haberman, Michael R.; Espalin, David; Wicker, Ryan; Lin, Yirong
Abstract: The additive manufacturing of piezoelectric ceramic Lead Zirconate Titanate (PZT) through paste extrusion 3D printing was demonstrated. Different paste compositions with varied water weight content were studied to find a composition suitable for printing. The pastes were evaluated in terms of their viscosities, yield stresses, and stability when aged. Furthermore, the material properties of the ceramics produced through paste extrusion were characterized and compared with those of ceramics fabricated through a conventional die pressing method. Paste extruded PZT with achieved densities as high as 94.9% of the theoretical density after sintering, which nearly matched the 95% density attained by the pressed samples. Upon poling, the paste extruded PZT piezoelectric ceramics attained piezoelectric coefficients and dielectric constants that were close to the values of die pressed samples. As near full density PZT ceramics were successfully fabricated through paste extrusion, this work paves the way for piezoelectric ceramics with application-driven geometry designs for sensors, actuators, and energy harvesters.